PENGARUH FAKTOR SOSIAL EKONOMI DAN MANAJERIAL TATAKELOLA PETERNAKAN TERHADAP KEBERHASILAN USAHA TERNAK SAPI PERAH (Suatu Kasus Pada Peternak Sapi Perah di Kecamatan Cipanas, Kabupaten Cianjur, Jawa Barat) - Ary Ridho Mustofa; Euis Dasipah; Karyana KS (Universitas Galuh, 2022)
This research aims to find out the influence of socio-economicactors of breeders and managerial breeders on the success of dairy farming efforts. The unit of analysis is a dairy farmer in Cianjur Subdistrict, Cianjur Regency. Respondents were taken in a census of 65 people. Analytical techniques are used pathanalysis. The results of the study obtained the state of the socio-economic factors of dairy farmers consisting of aspects / indicators: age, formal education, knowledge, experience, burden of dependents, motivation usaha, business scale and capital show good criteria with achievement of 71.54%. Managerial governance of dairy farmers consists of dimensions/ indicators: data collectionrecords, milking techniques, livestock health, feed, marriage, business governa nce, trade, labor and marketing show good criteria with an achievement of 78.88%. Against the managerial aspects of the breeder, the aspect / dimension of livestock health and business governance shows excellent criteria. The success of dairy farming business consisting of dimensions: Productivity of cows; Production costs; and efficiency of farming. During lactation the average dairy product produces milk reaching 22 liters / tail / day, the average production cost is Rp 2,250 / liter and the average business efficiency of 1.98. The success rate of dairy farming is 75.64%. There is a strong and tangible positive relationship between the socio-economic factors of breeders and managerial governance of breeders. The strong relationship between the two variables is indicated by the pearson correlation coefficient = 0.533. Socio-economic factors of breeders and managerial governance have a positive and real influence on the success of dairy farming efforts. Contribution of socio-economic factors 15.54% and managerial governance 45.14%. Much bigger.